Self-Control dan Cyberloafing: Tantangan Pengendalian Diri Karyawan di Era Digital (Studi pada PT Pindo Deli 2 Karawang) - Ghea Jingga Araya; Lania Muharsih; Holy Greata (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to determine the effect of self-control on cyberloafing behavior among employees of PT Pindo Deli Pulp & Paper Mill 2 Karawang. The method used was a quantitative approach with a causality design, as well as a non-probability sampling technique with a saturated sample method, where the entire population of 84 employees were used as respondents. The data collection instrument consisted of a Brief Self-Control Scale and a cyberloafing scale. Data analysis was carried out using simple linear regression, obtaining a significance value of 0.000 and an R² of 0.146. This means that 14.6% of the variation in cyberloafing behavior can be explained by the self-control variable. This means that the results of the analysis indicate that self-control has a significant positive influence on cyberloafing behavior.